ESTIMATION OF YIELD LOSSES IN COTTON DUE TO MAJOR FUNGAL FOLIAR DISEASES - SK ROSHAN BABA*, S.L. BHATTIPROLU, V. PRASANNA KUMARI and CH. CHIRANJEEVI, (The Journal of Research ANGRAU, 2022)
The experiment was conducted at Regional Agricultural Research Station, Lam, Gunturduring kharif 2019-20 to estimate the losses due to major fungal foliar diseases including Alternarialeaf spot, Corynespora leaf spot and grey mildew in two BG II hybrids and one straight variety ofcotton. Two sprays of propiconazole @ 0.1% were applied at 60 DAS and 75 DAS; third spraywith metiram + pyraclostrobin @ 0.1% at 90 DAS and final spray of carbendazim @ 0.1% wereapplied at 105 DAS. Disease observations were recorded to assess the severity of fungal foliardiseases of cotton in protected and unprotected plots. Percent increase in unprotected plotsvaried from 64.65 to 84.95, 85.77 to 87.12 and 70.59 to 78.40 when compared to plots protectedfor Alternaria leaf spot, Corynespora leaf spot and grey mildew, respectively. Yield data in protectedand unprotected plots revealed that percent seed cotton yield loss of 16.14 in Jaadoo BG II,20.34 in RCH 2 BG II and 26.28 in L 1060. The highest ICBR was obtained for Jaadoo BG II(26.61) when compared to RCH 2 BG II (19.95) and L 1060 (19.46).